PENGARUH VARIASI JUMLAH GARAM DAN WAKTU PENGGARAMAN TERHADAP KUALITAS VIRGIN COCONUT OIL (VCO) - Syauqul jannah (Jurnal Farmasi Medica/Pharmacy Medical Journal (PMJ), 2023)
Virgin Coconut Oil (VCO) is a processed product from fresh coconut meat that is processed at room temprature or without heating. VCO Oil can be used in various methods, namely heating method, acidification method, and fishing method. The purpose of this study was to determine the quality of VCO made by salting methods with variations in the amount of salt and the time of salting. In research, VCO oil is made by using variations in the salting time, namely 24, 36 and 48 hours and variations n the 1, 2 and 3 grams. The VCO oil obtained will then be subjected to organoleptic tests, free fatty acids, water content and pH tests. The results showed that the variation in the amount of salt and the time of drying had no effect on the organoleptic properties of the VCO oil, where the VCO had a yellowish color, a distinctive smell of coconut oil, and chemical properties tests including pH, water concet and ALB, variations in the amount of salt and the time of salting greatly affect the quality value of VCO oil.